FORMATION OF LANGUAGE CULTURE IN ENGLISH LANGUAGE TEACHERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Formation of language culture in English language teachers is one of the important aspects of the modern education system. Language culture mainly includes social, cultural and psychological aspects of language. The formation of language culture in English language teaching not only helps the language learning process, but also the development of students' culture, outlook and social skills. This process, in turn, enables global communication and cultural exchange.